LISPRO mitigates β-amyloid and associated pathologies in Alzheimer’s mice - Habib, Ahsan (Cell Death Dis, 2017)
Lithium has been marketed in the United States of America since the 1970s as a treatment for bipolar disorder. More recently, studies have shown that lithium can improve cognitive decline associated with Alzheimer’s disease (AD). However, the current United States Food and Drug Administration-approved lithium pharmaceutics (carbonate and citrate chemical forms) have a narrow therapeutic window and unstable pharmacokinetics that, without careful monitoring, can cause serious adverse effects. Here, we investigated the safety profile, pharmacokinetics, and therapeutic efficacy of LISPRO (ionic co-crystal of lithium salicylate and l-proline), lithium salicylate, and lithium carbonate (Li(2)CO(3)). We found that LISPRO (8-week oral treatment) reduces β-amyloid plaques and phosphorylation of tau by reducing neuroinflammation and inactivating glycogen synthase kinase 3β in transgenic Tg2576 mice. Specifically, cytokine profiles from the brain, plasma, and splenocytes suggested that 8-week oral treatment with LISPRO downregulates pro-inflammatory cytokines, upregulates anti-inflammatory cytokines, and suppresses renal cyclooxygenase 2 expression in transgenic Tg2576 mice. Pharmacokinetic studies indicated that LISPRO provides significantly higher brain lithium levels and more steady plasma lithium levels in both B6129SF2/J (2-week oral treatment) and transgenic Tg2576 (8-week oral treatment) mice compared with Li(2)CO(3). Oral administration of LISPRO for 28 weeks significantly reduced β-amyloid plaques and tau-phosphorylation. In addition, LISPRO significantly elevated pre-synaptic (synaptophysin) and post-synaptic protein (post synaptic density protein 95) expression in brains from transgenic 3XTg-AD mice. Taken together, our data suggest that LISPRO may be a superior form of lithium with improved safety and efficacy as a potential new disease modifying drug for AD.